Agricultural Extension Reforms in Kenya: Promoting Agri-Business through Value Chains - Mucoki, Shelmith Waruguru; 0. Nkurumwa, Agnes (Journal of Agricultural Extension Management, 2018)
In Kenya, the agriculture sector is the mainstay of the country’s economy and the role of the agricultural extension service in promoting growth in the agriculture sector is well recognized. Kenya’s extension service, like many other developing countries has been undergoing a number of reforms since the early 1990s in a bid to improve its effectiveness. The country has therefore tried a number of extension models and styles. The Agriculture Sector Development Support Programme (ASDSP) is the new agricultural extension model in Kenya and it is based on Agriculture Sector Development Strategy (ASDS). The overall goal is to support the transformation of Kenya’s’ agriculture sector into an innovative, commercially oriented, competitive and modern industry that contributes to poverty reduction, improved food and nutrition security in rural and urban Kenya, as a result of improved production and productivity in the rural smallholder farm and off-farm sectors through the value chain approach. The ASDSP has three components, and the third deals specifically with value chain development. The purpose of this paper is to share highlights on Kenya’s new agricultural extension reforms, which will transform the role of the agricultural extension service from simply focusing on agricultural production, to promotion of agri-business by focusing on the entire value chain. The strategy will create stronger ties with all players in the value chains through more effective networking and collaboration from national level to the counties, sub-counties and wards, which are the centres of implementation. The current extension reforms are expected to result in a more vibrant agriculture sector, with more of the small-scale farmers participating actively in market led economy and reaping greater benefits from the value chains.